THE IMPLEMENTATION OF IEPC STRATEGY TO IMPROVE STUDENTS' READING COMPREHENSION AT SMAN 10 SOLOK SELATAN - Mike Okmawati (SEAMEO QITEP in Language, 2023)
This study aims to describe the implementation of the IEPC strategy and to find out the effect of the IEPC strategy (imagination, elaboration, prediction, and confirmation) in improving students' reading comprehension and students' activities in learning at grade XI SMAN 10 Solok Selatan. This research was a Classroom Action Research (CAR) with Kemmis and McTaggart's design consisting of two cycles. The subjects of this study were students of grade XI IIS SMAN 10 Solok Selatan in the 2022/2023 academic year. The data were collected through tests and observation sheets. Data were analyzed by using quantitative descriptive analysis. The results revealed that the average score of pre-test was 58.5, the average score of post-tests in cycle I was 69.5 and the average score of post-tests in cycle II was 73.5. From the observation sheet, the average score of students’ activities in cycle I was 62% and in cycle II was 72%. It was concluded that the IEPC strategy's implementation improves students' reading comprehension and students’ activities in learning English. Thus, the teacher is suggested to apply this strategy to improve students’ reading comprehension.